2015
DOI: 10.1007/s12350-014-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of image reconstruction algorithms encompassing Time-Of-Flight and Point Spread Function modelling for quantitative cardiac PET: Phantom studies

Abstract: IR accounting for TOF and PSF can be recommended for the quantification of dynamic cardiac PET studies as they improve the results compared to analytic and standard IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Iterative reconstruction methods in PET, such as orderedsubset expectation maximization (OSEM) algorithm method with time-of-flight (TOF) and point spread function (PSF) modeling are now routinely employed in cardiac imaging [6][7][8]. In addition, regularized reconstruction methods based on Bayesian-penalized maximum likelihood (Q.Clear) have recently been introduced [9].…”
Section: Introductionmentioning
confidence: 99%
“…Iterative reconstruction methods in PET, such as orderedsubset expectation maximization (OSEM) algorithm method with time-of-flight (TOF) and point spread function (PSF) modeling are now routinely employed in cardiac imaging [6][7][8]. In addition, regularized reconstruction methods based on Bayesian-penalized maximum likelihood (Q.Clear) have recently been introduced [9].…”
Section: Introductionmentioning
confidence: 99%
“…Alternately, patient injected dose and patient scan duration, two major limitations of clinical PET systems, may both be substantially reduced with much better ToF performance (Fazel et al 2009). If less than 20 picosecond (<20 ps) time resolution were possible, image reconstruction time would also be greatly reduced (Presotto et al 2015, Mehranian et al 2016), enabling PET for real time imaging applications including guiding diagnostic interventions and surgical treatments for diseases. Additionally, significantly higher SNR enabled by better time resolution paves the way for advanced clinical PET systems designed with significantly smaller photon detector elements to increase spatial resolution for patient studies (Levin and Hoffman 1999).…”
Section: Introductionmentioning
confidence: 99%
“…14 Time-of-flight (TOF) methods combined with resolution recovery have been shown to improve quantification of dynamic cardiac PET compared to FBP and standard iterative reconstruction in a phantom study. 15 Recently, the suitability of the TOF reconstruction with resolution recovery was studied in patients for 13-N-Ammonia blood flow quantification. 16 The authors concluded that TOF allowed better visual image quality and contrast with TOF.…”
Section: Newer Techniquesmentioning
confidence: 99%